Impact Evaluation of Genotypes and Fertility Levels on Quality Traits, Nutrient Uptake, Yield and Economics of Single-Cut Fodder Sorghum [Sorghum bicolor (L.) Moench] - Gurjar, Gaurav Singh; Choudhary, Ram Swaroop; Jat, Gajanand; Choudhary, Roshan (International Journal of Bio-resource and Stress Management, 2019)
An experimentwas carried out at Instructional Farm, Rajasthan College of Agriculture, Maharana Pratap University of Agriculture & Technology, Udaipur (Rajasthan), India during July to September in Kharif, 2018 on sandy clay loam soil to evaluate the effect of genotypes and fertility levels on single-cut fodder sorghum with three objectives to select suitable single-cut fodder sorghum genotype, to workout optimum fertility levels and to arrive at economically viable treatment. Fifteen treatment combinations consisted of five genotypes i.e. SPV 2296, SPV 2316, SPV 2445, CSV 21F and CSV 30F with three fertility level i.e. 75, 100 and 125% RDF (100% RDF equals to 80 kg N+40 kg P2O5+40 kg K2O ha-1) were laid out in Factorial RBD and replicated thrice. Results indicated that among the single-cut fodder sorghum genotypes, SPV 2445 of performed better in respect to HCN % (0.0250 at 30 DAS & 0.0164 at harvest), chlorophyll at 50% flowering (1.99 mg g-1 fresh wt.), quality traits % (crude protein 7.07, crude fibre 30.01, ether extract 1.72, mineral ash 6.75), while maximum nitrogen free extract % (56.97) and total digestible nutrient % (56.27) were recorded with genotype SPV2296. Simultaneously, nutrient content and uptake, fodder yield (green 57.34 t ha-1and dry 14.22 t ha-1) and net return (Rs. 58375 ha-1) were also proved significantly superior with genotypes, SPV 2445 than other genotypes. The crop fertilized with 125% RDF performed better in respect to all the quality traits, nutrient (content & uptake), yield and economics.